Investigating the biochemical parameters and bone mineral density in active and sedentary adults - Karakuzulu M; Mendeş B; Çiçek H; Elboğa U; Mendeş M (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Propose: This study aims to identify the change in the relationship between biochemical parameters and bone mineral density (BMD) in adults with different sex and lifestyles. Methods: The sample group of the study consists of football players and sedentary men and women in the 18-25 age group, 80 participants in total. The participants were tested in terms of certain biochemical parameters such as glucose, insulin, creatinine, calcium, phosphorus, vitamin D, homocysteine, vitamin B12, folate and bone mineral density (BMD). Multidimensional Scaling Technique was used in investigating the relations between BMD and biochemical parameters. Results: Results of Multidimensional Scaling Analysis showed that there was a strong relationship in all groups between T and Z scores and other parameters except vitamin B12 and glucose levels. Conclusions: The biochemical parameters related to bone, muscle and heart health in football players were found more normal than sedentary group. While no significant gender-related difference was identified among the groups in terms of the relationship between BMD, T and Z scores of lumbar and femur areas and biochemical parameters.